Discovery of a missing intrauterine system in the peritoneal cavity during cervical cancer surgery: a case report - Restaino, Stefano; Poli, Alice; Arcieri, Martina; Della Martina, Monica; Scambia, Giovanni; Driul, Lorenza; Vizzielli, Giuseppe (Acta Biomedica Atenei Parmensis, 2024)
Background: Intrauterine devices (IUD) are the most commonly used form of long-acting, reversible contraception; however, they can rarely be complicated by perforation at insertion or migration. Migration in the abdomen can cause inflammation, fibrosis, chronic pain and can affect neighboring organs but it can also be asymptomatic. Methods: We report the case of a woman with a story of a missing levonorgestrel-releasing intrauterine device who didn’t undergo imaging to find the device and decided for the insertion of a second IUS. Then the missing device was discovered in her peritoneal cavity during surgery for cervical cancer. Results: The patient had at the same time the missing IUS in the peritoneal cavity and a correctly positioned IUS into the uterus and she had no symptoms related to the migrated IUS. Current literature reveals that up to 85% of patients with uterine perforation by IUD migration are asymptomatic. However, removal of the device is recommended, even in asymptomatic patients using minimally invasive methods if possible, including hysteroscopy, laparoscopy, cystoscopy, and colonoscopy depending on the location of the IUD. Conclusions: In a context of a missing IUD an abdominal imaging should be carried out to localize the device and its removal is recommended to avoid consequences.